POSITIONING FLOWER BOUQUET DENGAN MULTIDIMENSIONAL SCALING BERDASARKAN PERSEPSI KONSUMEN DI LACHERIE FLORIST - Mariana, Christy Dwita; Octavalery, Yolanda; Yusuf, Dionisius (Business, Economics dan Entrepreneurship, 2021)
The purpose of this study is to determine the position of flower bouquet on ​​the consumer perception in Lacherie Florist by using multidimensional scaling analysis (MDS). The sample in this research were 104 respondents of Lacherie Florist. Data collection used a questionnaire through Google forms. The validity test results stated that all statements were valid as well as the reliability test showed that all parameters were reliable. The results obtained from the bouquet flower were divided into four different positioning groups based on consumer perception. The results indicated that (1) Bloom Box was most different from other types of bouquet flower (2) Bloom Bag, Artificial Flowers and Snack Bouquet have similarities because they were in the same quadrant (3) Mixed Money and Flowers and Money Bouquet were the most similar type because of the position closest to each other. (4) Fresh flowers have similarities with Mix Money Bouquet and Flowers but located in different quadrant.Keywords: Bouquet flower, consumer, perception, multidimensional scaling, positioning